RELATIVE ABUNDANCE OF AGE GROUPS OF OILSARDINE AND ITS EFFECT ON FISHERY OF MANGALORE AREA - Dhulkhed, M H; Umakumari, K (Indian Journal of Fisheries, 2011)
Analyses of catch data on oil sardine from 1966-67 through 1976-77 indicated that the fluctuations in the fishery were closely related to the strength of different age groups. The fishery appeared to be good when the 0 and 1 year groups were equally and continually represented in the catches. The estimated average rate of instantaneous rate of mortality was 1-87.